Gain and pain: resilience of home mobility in early Shabiyat housing of Ras Al-Khaimah - Assi, Eman (Frontiers in Built Environment, 2023)
The Social Housing Program initiated by the UAE Government in 1971 is a program aiming to upgrade the living conditions of the local Emiratis. The early projects of these housing projects known later as Shabiyat. People who were living in a very harsh conditions in the mountains of Ras Al Khaimah found themselves willingly and within a short period relocated in new houses with approximate distance to their original homes, trying to adapt to the new life style and new place. Every day practice has changed. As result the degree of the resilience of their new houses are questioned. This paper will try to investigate the degree of resilience of the early housing of Shabiyyat. The research will open up the discussion on the notion of home mobility and how it is related to resilience through physical and nonphysical spatial transformation and everyday practice. The study is structured into two sections; the first section is about understanding the resilience of the traditional settlements in the mountains. The second part is about the main characteristics of early Shabiyat, its main concept and how it has addressed the needs of the Emirati society. this will help us to trace the pattern of resilience in these structures and offer some practical guidance for professionals and public sector in developing their policies towards maximizing the sustainability of any proposed future social housing projects.